Climate exposures and child undernutrition: Evidence from Indonesia. (November 2020) - Thiede, Brian C.; Gray, Clark
Abstract: Global climate change has the potential to disrupt agricultural systems, undermine household socioeconomic status, and shape the prevalence and distribution of diseases. Each of these changes may influence children's nutritional status, which is sensitive to food availability, access, and utilization, and which may have lasting consequences for later-life health and socioeconomic outcomes. This paper contributes to the emerging literature on climate and child health by studying the effects of temperature and precipitation exposures on children's height and weight in Indonesia. Drawing on five rounds of the Indonesian Family Life Survey (IFLS) implemented between 1993 and 2015, we estimate fixed-effects regression models of height-for-age (HFA) and weight-for-height (WFH) among samples of children ages 24–59 months and 0–23 months, respectively. We test for heterogeneity in these effects across sub-populations expected to vary in their vulnerability. Results show that delays in monsoon onset are consistently associated with worse child health outcomes. Delays in monsoon onset during the prenatal period are associated with reduced child height among children age 2–4 years. The weight of young (<2 years) children is adversely affected by delays in the most recent monsoon season, and this relationship is particularly strong among residents of Java. Overall, our results underline the need for interventions that protect children's nutrition and underlying health against the effects of climate change. Highlights: Climate variability has potential to influence nutrition through multiple pathways. Delays in the monsoon are associated with poor child health outcomes in Indonesia. Effects of monsoon delay exposure are robust, but vary across some social groups.